Highly oriented vertically aligned carbon nanotubes via chemical vapour deposition for key potential application in CNT ropes - Yousefi, A.T.; Bagheri, S.; Shinji, K.; Mahmood, M.R.; Ikeda, S. (Springer Verlag (Germany), 2015)
The remarkable properties of highly oriented vertically aligned carbon nanotubes (CNTs) make them attractive for electrical applications, especially for CNT ropes. In this paper, we describe the process to grow long oriented CNT arrays to improve the electrical properties of the devices based on CNTs. Chemical vapour deposition was used to deposit highly oriented CNTs using camphor oil as a carbon source and argon and hydrogen gas as carrier gases to grow perpendicular CNTs on the surface of the silicon substrate in presence of ferrocene as a metallic catalyst. Images obtained by field emission SEM indicate the formation mechanism of oriented CNTs with high morphological purity of nanotubes, which depends significantly on the deposition time and applied temperature to the furnaces. The TEM images confirm synthesis of multiwall CNTs (MWCNTs). This method might be an effective method of producing highly oriented MWCNTs in different aspect ratios.